2021
DOI: 10.1002/smll.202006387
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Zinc Oxide with Zirconium Doping for Efficient Inverted Organic Solar Cells

Abstract: Solution‐processed zinc oxide (ZnO) is one of the widely used electron transporting layers (ETLs) for organic solar cells (OSCs). However, low optical transparency along with thickness‐sensitivity of ZnO ETL constrains the improvement of photovoltaic performance and large‐scale fabrication compatibility. To resolve these issues, zirconium (Zr) doping is applied to tailor the optoelectronic and morphological properties of ZnO layer. This approach not only improves light transmittance with the suppressed parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…As we all know, high degree of crystalline order, good thermal stability and weak dependence on the thicknesses of interface are of significance for cathode interfacial materials to prepare efficient industrial OSCs. [33][34][35][36] Thus, it is highly desirable to develop a high quality cathode interlayer with low processing cost and simple synthesis route, enabling the potential commercialization of OSCs. [37] Herein, we developed three low-cost and simple imidebased molecules with different amine side-chains, namely Ndimethylaminopropyl-4-bromo-1,8-naphthalimide (NA), Ndimethylaminopropyl-4-dimethylaminopropylamino-1,8-naphthalimide (NAA), and N-dimethylaminopropyl-4-aminoethylamino-1,8-naphthalimide (NEA), used as cathode interlayers in OSCs (Scheme 1 and Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…As we all know, high degree of crystalline order, good thermal stability and weak dependence on the thicknesses of interface are of significance for cathode interfacial materials to prepare efficient industrial OSCs. [33][34][35][36] Thus, it is highly desirable to develop a high quality cathode interlayer with low processing cost and simple synthesis route, enabling the potential commercialization of OSCs. [37] Herein, we developed three low-cost and simple imidebased molecules with different amine side-chains, namely Ndimethylaminopropyl-4-bromo-1,8-naphthalimide (NA), Ndimethylaminopropyl-4-dimethylaminopropylamino-1,8-naphthalimide (NAA), and N-dimethylaminopropyl-4-aminoethylamino-1,8-naphthalimide (NEA), used as cathode interlayers in OSCs (Scheme 1 and Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it was noticeably observed that the In:CdS film displayed higher conductivity than the CdS film (Figure c,f). The enhanced conductivity of In:CdS confirmed the higher doping density, which originated from the additional In atom-generated electron because of the substitution of Cd 2+ by In 3+ . The increased doping density of In:CdS could induce stronger band bending and a built-in electric field, which boosts the carrier transport and further obtains improved device performance. ,, …”
Section: Resultsmentioning
confidence: 79%
“…The efficiency of 14.7 % for a non-fullerene OSC-based Zr-doped ZnO ETL has been achieved, which is higher than that of undoped ZnO ETL counterpart. [64] Other metal oxides such as Tin oxide (SnO x ), Cerium oxide (CeO x ), Alumina (Al 2 O 3 ), and Zirconia (ZrO 2 ), etc., insulating nanolayers can also be used to reduce the work function of cathode and promote charge collection in OSCs. [65][66][67]…”
Section: Electron Collection Interface Layermentioning
confidence: 99%